2014
DOI: 10.4103/0970-9185.130022
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine decreases requirement of thiopentone sodium and pentazocine followed with improved recovery in patients undergoing laparoscopic cholecystectomy

Abstract: Background:Pain relief remains the most fundamental and consequential aspect of surgery for patients throughout perioperative period. Dexmedetomidine has created an interest in α2-adrenoceptor agonists in the management of pain and hence the aim of this study was to evaluate the effectiveness of the drug in hilly population of North India.Materials and Methods:Patients, irrespective of gender, were randomly allocated to two groups, control and test, each having 30 patients. Test group received an infusion of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Collard et al, [22] reported that intraoperative esmolol infusion facilitates earlier discharge because of decrease opioid requirement. In our study also dexmedetomidine and esmolol group had significant reduction in induction dose of propofol and intraoperative fentanyl requirement compared to control group [11,13,23,24].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Collard et al, [22] reported that intraoperative esmolol infusion facilitates earlier discharge because of decrease opioid requirement. In our study also dexmedetomidine and esmolol group had significant reduction in induction dose of propofol and intraoperative fentanyl requirement compared to control group [11,13,23,24].…”
Section: Discussionmentioning
confidence: 66%
“…Several modifications in technique have been tried to attenuate these responses. Various pharmacological agents like nitroglycerine [4], beta blockers [5], opioids [6], gabapentin [7], pregabalin [8], magnesium sulfate [9], clonidine [10] and dexmedetomidine [11] are used to provide hemodynamic stability during pneumoperitoneum with varying success rate.…”
Section: Introductionmentioning
confidence: 99%
“…In another studies, an infusion of dexmedetomidine at the rate of 0.5 µg/kg/h 30 min before induction and 0.6 µg/kg/h thereafter until the end of surgery leads to better recovery of patients undergoing laparoscopic cholecystectomy. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine also causes a reduction in doses of propofol both during induction and maintenance. [ 2 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%